2017
DOI: 10.5586/am.1083
|View full text |Cite
|
Sign up to set email alerts
|

Puccinia passerinii (Pucciniales) on Thesium ebracteatum in the Biebrza National Park – new data on its distribution in Central Europe

Abstract: This work provides a morphological description of a parasitic fungus Puccinia passerinii Schroet. discovered in the Biebrza National Park on bractless toadflax Thesium ebracteatum Hayne, a host plant listed in Appendix II of the Habitat Directive and strictly protected in Poland. Puccinia passerinii was recorded in 1916 within the borders of current-day Poland, however, owing to a lack of herbarial materials it was not included into the checklist of Polish microscopic fungi. This work is the first report, afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Thus, molecular genetic studies have shown a high molecular dispersion between individuals of different populations and an average in the populations themselves, as well as a direct dependence of the value of intrapopulation genetic diversity on the size of the population (Dostálek et al, 2014). The distribution of the phytopathogenic fungus Puccinia passerinii Schroet was studied on T. ebracteatum (Sucharzewska et al, 2016). Mostly, pregenerative shoots affected by the fungus were noted, on which premature death of leaves occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, molecular genetic studies have shown a high molecular dispersion between individuals of different populations and an average in the populations themselves, as well as a direct dependence of the value of intrapopulation genetic diversity on the size of the population (Dostálek et al, 2014). The distribution of the phytopathogenic fungus Puccinia passerinii Schroet was studied on T. ebracteatum (Sucharzewska et al, 2016). Mostly, pregenerative shoots affected by the fungus were noted, on which premature death of leaves occurred.…”
Section: Introductionmentioning
confidence: 99%